2002
DOI: 10.1021/ol026260y
|View full text |Cite
|
Sign up to set email alerts
|

Studies Aimed at the Total Synthesis of Azadirachtin. A Modeled Connection of C-8 and C-14 in Azadirachtin

Abstract: [reaction: see text] Studies on the connection between the right and left segments of azadirachtin are described. The Ireland-Claisen rearrangement of Li-enolate of the modeled ester with dichlorodimethylsilane in toluene afforded the desired limonoid framework stereoselectively in good yield.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 25 publications
0
25
0
2
Order By: Relevance
“…This was surprising given that simple trialkylamines are particularly feeble ligands 2, 3a,b ,4 that have rarely been used in organolithium chemistry. 5,6 The high rates imparted by trialkylamines were traced to a dimer-based pathway exemplified by transition structure 3. The exceptional steric demands of the trialkylamines were shown to destabilize dimeric LiHMDS reactants more than they destabilize transition structure 3.…”
Section: Introductionmentioning
confidence: 99%
“…This was surprising given that simple trialkylamines are particularly feeble ligands 2, 3a,b ,4 that have rarely been used in organolithium chemistry. 5,6 The high rates imparted by trialkylamines were traced to a dimer-based pathway exemplified by transition structure 3. The exceptional steric demands of the trialkylamines were shown to destabilize dimeric LiHMDS reactants more than they destabilize transition structure 3.…”
Section: Introductionmentioning
confidence: 99%
“…In this strategy the A-ring 25 could be merged with the bicyclic C–D system 26 by esterification in order to obtain the allyl ester rearrangement precursor 24 . Murai et al [48] showed the utility of an Ireland–Claisen rearrangement in their model studies addressing the limonoid framework of azadirachtin.…”
Section: Resultsmentioning
confidence: 99%
“…[86] Stereocontrolled pre-installation of a tethered syn-1,3-diol moiety onto the IMDA precursor 189 was strategically implemented to secure the A-ring diaxial diol configuration of 150, without the need for diastereoselective oxidation state adjustments at a later stage. In addition to demonstrating access to a viable advanced tricyclic western intermediate (190) of azadirachtin in only 18 steps [86] (from ethyl malon- Scheme 21. ate), an Ireland-Claisen rearrangement strategy was also successfully executed [88] to connect C8 with C14 in a highly functionalized model system (191) with excellent stereocontrol. [87] On exposure to the in situ-derived B-allyldiisopinocampheylborane reagent, [87] the dioxane-carbaldehyde 183 (prepared in seven steps from ethyl malonate) underwent smooth allylation to provide alcohol 184 with high optical purity due to minimization of 1,3-diaxial interac-tions in the chairlike transition state (TS-I).…”
Section: The Murai Intramolecular Diels-alder (Imda) Approach To Azadmentioning
confidence: 99%